2021
DOI: 10.5114/hm.2021.103290
|View full text |Cite
|
Sign up to set email alerts
|

The effects of perceived competence and self-controlled goal setting on motor learning

Abstract: Purpose. On the basis of the assumptions that motor learning involves a process in which the learner gains competence on a task, and perceived competence is closely related to the achievement of a goal and the perception of control, this study investigated the effects of perceived competence and self-controlled goal setting on motor learning. Methods. Sixty right-handed volunteers, both male (n = 28) and female (n = 32), with an average age of 26.35 years (± 6.29) took part in this experiment. the motor learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Finally, previous studies showed improved success perception when learning involved lower difficulty goals (Ong, Hawke & Hodges, 2019) and even better learning than difficult goals (Iwatsuki & Regis, 2020). However, Carvalhais et al (2021) showed that learning is better when perceived competence is high. Our results show that perceived sports competence mediates learning sports motor skills with higher difficulty goals.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Finally, previous studies showed improved success perception when learning involved lower difficulty goals (Ong, Hawke & Hodges, 2019) and even better learning than difficult goals (Iwatsuki & Regis, 2020). However, Carvalhais et al (2021) showed that learning is better when perceived competence is high. Our results show that perceived sports competence mediates learning sports motor skills with higher difficulty goals.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, perceived competence and goalsetting difficulty have been investigated in recent years. Studies have suggested that less difficult goals improve success perception but do not differentiate learning (Iwatsuki & Regis, 2020) and that higher perceived competency is better for learning (Carvalhais, Silva, Tani & Corrêa, 2021). In addition, the studies did not investigate whether the perception of competence is a mediator of learning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Effect of boteli and frequency modification exercise in improving groundstroke forehand really skills in tennis 276 points are earned through groundstroke rallies, so this technique becomes the most important hit and a key factor in the game's success (Fett et al, 2021). There are so many basic techniques in the game of tennis, but one of the most important basic techniques that tennis athletes must master is groundstroke because, in a game, the method of hitting is most often done by players (De Almeida Carvalhais et al, 2021). Not only can you do this, but a player must have good hitting accuracy in order to get points and win the game.…”
Section: Agustiyantomentioning
confidence: 99%